E-Tutorial: Pemodelan Dan Simulasi Respon Transien Arus Dan Tegangan Pada Rangkaian RLC Menggunakan ATPDraw - Iswadi HR; Suwitno Suwitno (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
Abstract The aim of this paper is to depelove teaching aid for Electrical Circuit subject. Voltage and current transient analysis in RLC series circuit had been coohsen as examples. It used ATPDraw for analyzing and modeling the circuits. It is hoped that by using this teaching aid and simulation, the result of voltage and current transient in an electrical circuit will be obtained easly and fastly than hand calucated method. The final product of this teaching aid will be converted to a video tutorial. Using this video tutorial, the students can review the subject by themselve. Finally, it is hoped that using this video tutorial, the student’s understanding in electrical circuit subject will increase. All of simulation results in these cases study had been compared to hand calculated method and other software (mathcad). From the graphs results, ATPDraw has the same result with mathcad simulation. Key words: E: Tutorial, Transient Responses RLC Circuit, ATPDraw, Mathcad